Respuesta :

Answer:

e=+5

Step-by-step explanation:

119=7(2e+7)

We move all terms to the left:

119-(7(2e+7))=0

We calculate terms in parentheses: -(7(2e+7)), so:

7(2e+7)

We multiply parentheses

14e+49

Back to the equation:

-(14e+49)

We get rid of parentheses

-14e-49+119=0

We add all the numbers together, and all the variables

-14e+70=0

We move all terms containing e to the left, all other terms to the right

-14e=-70

e=-70/-14

e=+5

Step-by-step explanation:

the other answer is right but it seems a bit overly complicated how the result was achieved.

119 = 7(2e + 7)

119 = 14e + 49

70 = 14e

e = 70/14 = 5

that's really it.